Organoids can be established reliably from cryopreserved biopsy catheter-derived endometrial tissue of infertile women. Issue 3 (September 2020) - Bui, Bich Ngoc; Boretto, Matteo; Kobayashi, Hiroto; van Hoesel, Marliek; Steba, Gaby S.; van Hoogenhuijze, Nienke; Broekmans, Frank J.M.; Vankelecom, Hugo; Torrance, Helen L.
Abstract: Research question: Can organoids be established from endometrial tissue of infertile women and does tissue cryopreservation allow for establishment of organoids comparable to organoids derived from freshly biopsied endometrial tissue? Design: Endometrial tissue was obtained from six infertile women through minimally invasive biopsy using a Pipelle catheter and subjected to organoid development, immediately after biopsy as well as after tissue cryopreservation. Organoid formation efficiency, morphology, expandability potential, endometrial marker expression (immunostaining and reverse transcription quantitative real-time polymerase chain reaction) and hormonal responsiveness (after oestradiol and progesterone treatment) were assessed. Results: Organoids established from both fresh and frozen tissue at comparable efficiency could be passaged long-term and showed similar morphology, i.e. cystic with a central lumen lined by a single epithelial cell layer. They also exhibited comparable expression of endometrial markers and proliferative activity (Ki67 expression). Finally, organoids from freshly biopsied and cryopreserved endometrial tissue showed similar responses to oestradiol and progesterone treatment. Conclusions: Organoids can be established from cryopreserved endometrial tissue of infertile women and cryopreservation of the biopsy does not affect organoid formation and overall organoid characteristics. Cryopreservation of biopsies for later organoid development facilitates sample collection from any fertility clinic, not just the ones near an organoid laboratory.